THE INFLUENCE OF THE LEPTIN GENE ON MILK PRODUCTION IN THREE CONSECUTIVE LACTATIONS IN HOLSTEIN FRIESIAN CATTLE - Esmerov, Igor; CHrcheva - nikolovska, Radmila; Markov, Nikolay; Uzunov, Risto; Angelovski, Ljupcho; Angeleska, Aleksandra; Mickov, LJupcho (Faculty of Agriculture, University of East Sarajevo, Republic of Srpska, Bosnia and Herzegovina..., 2025)
This study uses a PCR method to detect allelic polymorphisms of the LEP gene. The study was conducted among 100 Holstein cows owned by private breeders. The study was conducted on Pelagonija farm, located in the Southwestern part of Republic of North Macedonia, over a period of three lactations or 915 days. The research focused on the health status of the animal and animal welfare. This study will identify all genotypes of the LEP gene and determine associations between the polymorphism of the leptin gene and the dynamics of milk production during three lactations of the cows. The best indicators for all three lactations will be identified in the group of animals with the TT genotype of the LEP gene. These individuals are characterized by increased milk yield, a high yield index and a tendency to increase the average daily milk yield during three lactations. In cattle, the LEP gene provides instructions for synthesizing leptin, a protein hormone predominantly expressed by white adipocytes (fat cells). Leptin's physiological roles include the regulation of energy intake, body mass, immune competence, and reproductive function. Its mechanism involves binding to receptors in the lateral hypothalamus to curb appetite and to those in the medial hypothalamus to induce satiety. Genetic variations within the LEP gene have been implicated in modulating circulating leptin concentrations and are associated with economically significant production characteristics, such as milk yield and quality.
Keywords: milk production, LEP gene, leptin polymorphism, dairy cattle.